OVERCOMING THE LITERACY CRISIS AND IMPROVING CRITICAL THINKING SKILLS AT SDN 8 SUBULUSSALAM - Hermalinda, Hermalinda; Sari, Siti Mayang (SENSEI RESEARCH CENTER, 2024)
Basic education in Indonesia has an important role in forming the foundation of knowledge and character of children as the nation's next generation. Even though basic education in Indonesia has a vision and mission to create intelligent and characterful students, SDN 8 Subulussalam faces a number of challenges, especially related to the literacy crisis and the lack of development of critical thinking skills among students. The literacy crisis at SDN 8 Subulussalam is a fundamental problem that affects students' ability to read, write and understand various forms of text. The aim of this research is to describe Overcoming the literacy crisis and improving critical thinking skills at SDN 8 Subulussalam. This research uses a qualitative approach and descriptive research type. Based on the research results, it shows that SDN 8 Subulussalam faces significant challenges related to limited access to reading materials and students' lack of interest in reading. Concrete efforts by teachers, such as increasing library collections and collaborating with the community, have increased student interest, while the integration of learning methods for critical thinking skills and the use of technology is recognized as a positive step in overcoming the literacy crisis.